Demographic differences in International students' information source uses and everyday information seeking challenges - Sin, Sei-Ching Joanna (2015)
International students are a sizeable user group of academic libraries. However, their everyday life information seeking (ELIS) behavior is seldom studied. This hinders the planning of information services and information literacy training. In light of this gap, this study surveyed 112 international students in a U.S. public university on: (1) how frequently respondents used 11 information sources; (2) how difficult it was to find information in various domains; and (3) how much their ELIS was affected by various information seeking problems. Differences between gender-study level categories and problem solving styles were tested using ANOVAs. The study found that Web search engines, social networking sites, new friends, printed resources, and traditional mass media were the top sources for ELIS. Six everyday information domains (e.g., legal, financial, and personal development information) ranked more difficult to find than academic information. Non-credible, irrelevant, and outdated information were found to be the top problems. There were more statistically significant problem solving style differences (especially on the Problem Solving Confidence subscale) than gender-study level differences. Notable gender-study level differences were still found. Male undergraduate students, for example, were more affected by their reluctance to ask personal questions. Lastly, the implications to information literacy education were discussed.